Determinan Nilai Perusahaan Perbankan: Informasi Digitalisasi, Pengungkapan Modal Intelektual, dan Inovasi Produk Hijau - David Gabriel; Juniati Gunawan (Economic Reviews Journal, 2026)
This study evaluates the contribution of Digitization Information, Intellectual Capital Disclosure, and Green Product Innovation in optimizing firm value within the banking industry listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Employing a quantitative research design, secondary data were gathered from annual and sustainability reports. Based on the purposive sampling method and outlier adjustments, 42 banks were selected, yielding a total of 200 observations. Panel data regression with a Fixed Effect Model (FEM) estimation was applied as the analytical tool. The findings indicate that transparency regarding Digitization Information and the implementation of Green Product Innovation are proven effective in enhancing firm value through positive market response and investor confidence. Conversely, Intellectual Capital Disclosure, alongside ROA and Firm Size, does not show a significant impact on firm value. This study confirms the validity of Signaling Theory and the Resource-Based View (RBV) regarding the importance of resource management and strategic communication to investors.